Two new species of Elmidae (Coleoptera) from Argentina - Manzo, V.; Archangelsky, M. (Zootaxa, 2012)
Two new species of riffle beetles, Austrelmis patagonicus sp. nov. and Neoelmis argentinensis sp. nov. are described andillustrated from adults of both sexes. The mature larva of N. argentinensis is described and illustrated, and compared toother known larvae of Neoelmis. The distribution of the known species of Austrelmis and Neoelmis are synopsized and a checklist of the genera and species of Elmidae known from Argentina is given.